L'Església i la sinagoga als murals romànics d'Abu Gosh (Emmaús) i de Sixena - Pagès i Paretas, Montserrat (Miscel·lània litúrgica catalana, 2019)
In the Romanesque frescoes at Abu Gosh (Emmaus) in Palestine and at Sigena in the territory of the Crown of Aragon, there appears an extraordinary iconographic model, since it represents the church and the synagogue next to the crucified Christ. Both Abu Gosh and Sigena were monastic communities of the Order of Knights of the Hospital of Saint John of Jerusalem, built at the apogee of the order's power. These two paintings, which are stylistically quite similar, date from the last quarter of the 12th century those of Abu Gosh from before 1187 and those of Sigena from around 1196. This study focuses on the origins, use and expansion of the subject, and on its singular but identical depiction in the two monastic houses.